PENGARUH EKSTRAK DAUN RANDU (Ceiba pentandra) TERHADAP PROSES PENYEMBUHAN LUKA SAYAT PADA MENCIT (Mus musculus L) - Jezmy, Beby Kelidia; Oktarlina, Rasmi Zakiah; Sari, Ratna Dewi Puspita; Kurniawati, Evi (Medula, 2025)
Wound causes mechanical bleeding, inducing a response of the body to fix itself which undergoes a wound healing process through a few phases; hemostasis, inflammation, proliferation, and maturation or remodelling. Wound healing is a complex process due to biocellular and biochemistry activities occuring continously. One of the natural treatments is the administration of randu (Ceiba pentandra) leaf, a Spermatophyte which has been identified and used for its healing properties. This study was an experimental study with a post-test-only control group design, and datas were analyzed using a non-parametric Kruskal Wallis test. Treatments were given randu (Ceiba pentandra) leaf extract, grouped into 4: (K1): a negative control group, (P1): 40 ml of randu (Ceiba pentandra) leaf extract, (P2): 60 ml of randu (Ceiba pentandra) leaf extract, and (P3): 80 ml of randu (Ceiba pentandra) leaf extract. Through this study, randu (Ceiba pentandra) leaf extracts were rated based on the its wound healing rate and showed results of 80 ml, 60 ml, and 40 ml respectively. There is an effect of administration of randu (Ceiba pentandra) leaf extract on cut wound healing in mice (Mus musculus L) (p=0,037)